Investigation of Some Antibiotic Residue Levels in Honey Produced in Ardahan Province - Ertan DOĞAN (ISPEC Journal of Agricultural Sciences)
Beekeeping has been a major agricultural activity since ancient times. The importance of beekeeping is still present in our country, just like in other parts of the world. Honey, beeswax, pollen, propolis, royal jelly, and bee venom are the products produced by beekeeping. Honey is particularly important for human nutrition among these. It is crucial that the honey is free of antibiotics and other residues for this reason. The purpose of this study is to determine the level of residues of certain antibiotics (tetracycline and sulfonamide group) in honey produced in Ardahan province. As part of the research, honey samples from beekeepers in Ardahan and its counties (Göle, Çıldır, Hanak, Damal, and Posof) were collected in August 2023. 90 honey samples were collected from 15 different apiaries operating in each settlement. The residue level of tetracycline and sulfonamide group antibiotics in the honey samples collected directly from the producers was determined using the ELISA method. In this study, tetracycline and sulfonamide group antibiotic residues were not found in any of the 6 centers sampled, namely Ardahan, Göle, Çıldır, Hanak, Damal, and Posof. The research concluded that the honey that is produced in Ardahan province is safe for human health. It is thought that it would be useful to provide training to beekeepers on the subject in order to maintain healthy honey (free of antibiotics and other residues) production in Ardahan province.